2020
DOI: 10.1016/j.breast.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant regional nodal irradiation did not improve outcomes in T1-2N1 breast cancer after breast-conserving surgery: A propensity score matching analysis of BIG02/98 and BCIRG005 trials

Abstract: Aim To determine whether the addition of regional nodal irradiation (RNI) to whole-breast irradiation (WBI) would improve outcomes over WBI alone in T1-2N1 breast cancer after breast-conserving surgery (BCS) and adjuvant systematic therapy. Methods Data were obtained from two randomized controlled trials (NCT00174655 and NCT00312208). Univariate and multivariate Cox-regression analysis were performed to investigate predictors for overall survival and disease-free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The value of RNI in patients with T1-2N1M0 breast cancer remains a topic of great clinical relevance and controversy. Our results showed that the 5-year LRR was 7.2% in patients with T1-2N1M0 breast cancer without RNI, which is consistent with other contemporary studies showing that the 5-year LRR was less than 10% (9,(17)(18)(19). Given the low LRR risk, the necessity of RNI in T1-2N1M0 breast cancer has been questioned.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The value of RNI in patients with T1-2N1M0 breast cancer remains a topic of great clinical relevance and controversy. Our results showed that the 5-year LRR was 7.2% in patients with T1-2N1M0 breast cancer without RNI, which is consistent with other contemporary studies showing that the 5-year LRR was less than 10% (9,(17)(18)(19). Given the low LRR risk, the necessity of RNI in T1-2N1M0 breast cancer has been questioned.…”
Section: Discussionsupporting
confidence: 89%
“…Because IMN involvement occurred more frequently in patients with medially located tumors ( 31 ), coverage of IMN in RNI might be considered. One previous study showed that supraclavicular or IMN irradiation alone did not improve survival outcomes in N1 breast cancer ( 18 ). A Danish study showed that additional IMN irradiation significantly improved the OS in patients with one to three positive nodes and medially located tumors ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PSM was used to eliminate the effects of non-random statistics. We used 1:1 nearest-neighbor matching, setting the caliper as 0.02 to balance the baseline covariates within the groups (12). The 79,214 patients' characteristics between central and noncentral groups were compared by chi-square test.…”
Section: Methodsmentioning
confidence: 99%
“…Tangent field RT and systemic therapy provide good locoregional control for low risk cN0 patients with 1–2 positive SLN, in spite of the inadequate dose coverage of level I–II regions [ 2 ]. In the propensity score matching analysis of BIG02/98 and BCRG005 trials regional nodal irradiation (RNI) did not improve outcomes [ 25 ]. However, in these trials RNI was given after ALD and the target volume was the anatomic site of the dissected axillary lymph nodes.…”
Section: Discussionmentioning
confidence: 99%